The Relationship Between Advertising-Induced Anger and Self-efficacy on Persuasive Outcomes: A Test of the Anger Activism Model Using the Truth Campaign. Issue 1 (January 2017) - Ilakkuvan, Vinu; Turner, Monique Mitchell; Cantrell, Jennifer; Hair, Elizabeth; Vallone, Donna
Abstract : Turner's Anger Activism Model (AAM) contends anger and efficacy interact in a unique way to determine message responses to campaign materials. This study tested the AAM using responses to 2 truth antismoking advertisements collected in August-October 2014 via an online, cross-sectional survey of 15- to 21-year-olds. Those aware of each of the truth advertisements (n = 319 for each) were organized into 4 anger/efficacy groups. Analysis of variance and regressions were conducted to understand group differences in message-related cognitions (persuasiveness, receptivity, conversation). Message cognitions were highest among the high anger/high efficacy group and lowest among the low anger/low efficacy group.